An Application of Game Theory in Determining Competitive Strategies on Smartphone Products - Destia Anisya Ramdani; Jauhari Arifin (Jurnal Serambi Engineering, 2021)
In this modern era where technologies growing rapidly, various businesses are increasingly competitive as well as businesses in telecommunications. Nowadays, most of the companies manufacture sophisticated smartphones in which each of them has its own specialties to attract consumers. This studi aims to identify how each type of smartphone show its excellence so that it can make people interested. The purpose of this study is to find out how the implementation of game theory in determining the competitive strategies of each smartphone products. The results that is obtained from the Dominant method and the Maximin - Minimax method show that the optimal solution strategy obtained is 3, where 3 means explaining that the optimal solution from Xiaomi is the Price strategy (H), while Oppo with the quality strategy (K).